Penggunaan Konfiks ke-an dalam Wattpad Tanah Baghdad Karya Berliana Kimberly - Annaba Tri Siti Fadillah; Faiha Qotrunnada; Rayna Nurahma Sudariana; Rio Saputra; Encep Kusumah (Universitas Palangka Raya, 2026)
This research is motivated by the need to understand the change of morphophenmics as well as changes in the meaning of the confix in popular digital literature. Therefore, the purpose of this study is to describe in detail the characteristics of the confiscism of the fine in the wattage of the work entitled the Land of Baghdad by the Diamond Kimberly, with a focus on the rules of sound change, the way of word formation, and its grammatical meaning. The data in the study was taken from the digital corpus on Wattpad on the story of the Land of Baghdad, which was analyzed using distribution methods and paraphrases. The findings from this study show the presence of three rules of sound change when the confix is used in the word polymorphemy, with identified alomorphism including ke-yan, ke-wan, and psy. From the point of view of the grammatical function, the confix is proven to have derivasional and inflectional properties. Meanwhile, in terms of grammatical meaning, this confix is able to express the five main meanings, namely describing abstract properties and states, secondary meaning or visual appearance, conditions caused by accident, intensity of excess, and meaning related to a particular process, subject, or event. It is hoped that the results of this study can enrich the study of Indonesian morphology, especially in mapping the development of phonological distribution and semantic dynamics of the confse and conjecture in modern literary languages.